Health Care in the Information Society: What Should Be the Role of Medical Informatics?1 - Haux, R. (Methods of Information in Medicine, 2002)
Objective: To discuss the consequences for medical informatics in encouraging and advancing the development of information processing methodology (IPM) and information and communication technology (ICT) to contribute to high-quality and efficient health care.Methods: Characterization of the current state of ICT, commenting on literature.Results and conclusions: Medical informatics is the discipline, concerned with the systematic processing of data, information, and knowledge in medicine and health care. Our societies are continuously being influenced by modern IPM and ICT. It can be expected that these developments, leading us into an “information society”, will continue. Three factors may significantly influence health care in the near future: the development of the population towards an aging society, progress in medicine, and progress in informatics. The major aims that will have to be achieved are the (1) patient-centered use of medical data, (2) process-integrated decision support, using high-quality medical knowledge, and (3) comprehensive use of patient data for clinical research and health reporting. Medical informatics research is needed on the electronic patient record, modern architectures for health information systems, and medical knowledge bases. In order to adequately pursue the goal of “transforming health care through innovative use of ICT for the 21st century”, health care professionals are needed, who are well-trained in medical informatics, respectively health informatics. Medical informatics must offer such educational programs and assure a sufficiently high quality of education.
Keywords: Health care; health information systems; information and communication technology; medical informatics education; health informatics education